Assessment of MLL methyltransferase gene expression in larynx carcinoma - Figueiredo, David Livingstone Alves (2015)
Larynx cancer is the second most common type of cancer among all head and neck cancers. Deregulation of epigenetic effectors, including altered expression of histone methyltransferases from the MLL (mixed lineage leukemia) family, have been reported in many cancer types, yet little is known concerning their involvement in larynx cancer. Our objective was to determine the expression profile of MLL genes in larynx carcinoma and normal adjacent tissues and correlate this profile to tumor characteristics. We analyzed the expression profile of 5 MLL genes in 13 cases of larynx carcinoma and their adjacent non-tumor tissues using quantitative real-time PCR. MLL3 was significantly downregulated in tumor samples compared to their normal counterparts, and all MLL genes showed decreased expression in advanced tumors compared to tumors in the initial stage. Altered expression in a single MLL gene was associated with a similar alteration in the other MLL genes, revealing a strong correlation of expression in each individual patient. In conclusion, MLL genes may have similar transcriptional control, and decreased expression of these genes may contribute to larynx cancer progression.